A copper(I)-catalyzed addition/annulation sequence for the two-component synthesis of γ-ylidenebutenolides - Seo, S; Willis, M (American Chemical Society, 2017)
A highly efficient Cu(I)-catalyzed addition/annulation sequence has been developed for the synthesis of (Z)- ylidenebutenolides employing readily available α-ketoacids and alkynes as substrates. The reactions employ a simple commercially available Cu(I)-catalyst, display good substrate scope and deliver products with high stereoselectivity. The synthetic utility of the method is demonstrated by the straightforward derivatization of the ylidenebutenolides into a diverse range of heterocycles, and also by the preparation of the natural product bovolide, and analogs thereof.